The bioequivalence of fixed-dose combination tablets of bisoprolol and ramipril and its drug-drug interaction potential - Sus, Jan; Huguet, Jade; Bosak, Jan; Setnik, Beatrice; Hauser, Tomas; Sicard, Eric (Clinical and translational science, 2022)
Chronic antihypertensive treatment often includes combination of two or more therapies with complementary mechanism of action targeting different blood pressure (BP) control system. If available, these components are recommended to be administered as a fixed-dose combination (FDC) to reduce tablet burden, improve adherence and thus BP control. A combination of ramipril (RAMI) and bisoprolol (BISO) is one of the options used in clinical practice and is supported by therapeutic guidelines. The clinical program for a novel BISO/RAMI FDC consisted of two randomized, open-label, bioequivalence (BE) studies and one drug-drug interaction (DDI) study. The BE was examined between two FDC strengths of BISO/RAMI (10/10 and 10/5 mg) and the individual reference products administered concomitantly at respective doses after a single oral dose under fasting conditions. In both BE studies, 64 healthy subjects were randomized according to a two-way crossover design. The DDI study evaluated a potential pharmacokinetic (PK) interaction between BISO 10 mg and RAMI 10 mg following their single or concomitant administrations in 30 healthy subjects under fasting condition. BE for BISO/RAMI 10/5 mg and absence of a clinically relevant PK DDI between BISO and RAMI was demonstrated as the 90% confidence intervals (CIs) of the geometric mean ratios (GMRs) for area under the concentration time curve (AUC) and maximum concentration (Cmax ) remained within the acceptance range of 80.00 to 125.00%. However, BE for BISO/RAMI 10/10 mg was not demonstrated, as the lower bound of the 90% CI of Cmax for RAMI was outside the acceptance range of BE. Both drugs administered alone or combined were well-tolerated. No PK interaction was observed between BISO and RAMI/ramiprilat, since the co-administration of BISO and RAMI 10 mg single doses resulted in comparable rate and extent of absorption for BISO and RAMI when compared to their individual products.
Keywords: dospělí; bisoprolol; Female; terapeutická ekvivalence; lékové interakce; Drug Interactions; Adult; mladý dospělý; ženské pohlaví; Adolescent; lidé; Therapeutic Equivalency; ramipril; Bisoprolol; Male; Ramipril; Young Adult; kombinovaná farmakoterapie; lidé středního věku; Antihypertensive Agents; mužské pohlaví; antihypertenziva; Middle Aged; mladiství; Drug Therapy, Combination; Humans